Well‐dispersed polyurethane/cellulose nanocrystal nanocomposites synthesized by a solvent‐free procedure in bulk. (1st February 2018) - Kupka, Vojtěch; Zhou, Qi; Ansari, Farhan; Tang, Hu; Šlouf, Miroslav; Vojtová, Lucy; Berglund, Lars A.; Jančář, Josef
Abstract : Polyurethane (PU) nanocomposites utilizing cellulose nanocrystals (CNCs) as nanofiller and amorphous PU matrix were synthesized in a novel solvent‐free bulk process. A green nanofiller, CNCs, was studied as reinforcement and was further modified by grafting poly(ethylene glycol) (PEG) on the CNC surface (CNC‐PEG). Transmission electron microscopy revealed an excellent dispersion of the PEGylated CNC nanoparticles in the PU matrix, whereas as‐received CNCs formed agglomerates. The results indicated strong improvements in tensile properties with Young's modulus increasing up to 50% and strength up to 25% for both, PU/CNC and PU/CNC‐PEG nanocomposites. The enhanced tensile modulus was attributed to stiff particle reinforcement together with an increase in glass transition temperature. POLYM. COMPOS., 40:E456–E465, 2019. © 2018 Society of Plastics Engineers